Pengembangan E-Modul Berorientasi Strategi Flipped Classroom pada Pembelajaran Jaringan Komputer - Abna Hidayati; Andra Saputra; Raimon Efendi (Ikatan Ahli Informatika Indonesia (IAII), 2020)
The learning process is essentially a communication process that’s carried out synchronously and asynchronously. The results of observations in the Computer Network Engineering course, there are problems that the lecturer is not present, the learning resources used printed materials, as well as the existing books not updated and the sources are not by the syllabus so that the impact on student learning outcomes is low. E-Module is equipped with audio, video, images, and animation. The purpose of this study is to produce an E-Module in Valid, Practical, and Effective Computer and Network Engineering courses. This type of research is Research and Development with the ADDIE development model. The research data were obtained from tests of validity, practicality, and effectiveness. The results of the validity of the E-Module scored 93.3%, the results of the practicality assessment were obtained through questionnaire assessment by lecturers with a score of 96% and an assessment by students with score 91.7%. The Flipped Classroom Strategy-oriented E-Module was considered effective in increasing student motivation and learning outcomes, an average score of 91.6% for student activities was obtained. Based on the data above, the E-Module in Computer and Network Engineering courses is valid, practical, and effective for use in the lecture process.